Excess NF-κB Induces Ectopic Odontogenesis in Embryonic Incisor Epithelium. (January 2015) - Blackburn, J.; Kawasaki, K.; Porntaveetus, T.; Kawasaki, M.; Otsuka-Tanaka, Y.; Miake, Y.; Ota, M.S.; Watanabe, M.; Hishinuma, M.; Nomoto, T.; Oommen, S.; Ghafoor, S.; et al.
Nuclear factor kappa B (NF-κB) signaling plays critical roles in many physiological and pathological processes, including regulating organogenesis. Down-regulation of NF-κB signaling during development results in hypohidrotic ectodermal dysplasia. The roles of NF-κB signaling in tooth development, however, are not fully understood. We examined mice overexpressing IKKβ, an essential component of the NF-κB pathway, under keratin 5 promoter ( K5-Ikkβ ). K5-Ikkβ mice showed supernumerary incisors whose formation was accompanied by up-regulation of canonical Wnt signaling. Apoptosis that is normally observed in wild-type incisor epithelium was reduced in K5-Ikkβ mice. The supernumerary incisors in K5-Ikkβ mice were found to phenocopy extra incisors in mice with mutations of Wnt inhibitor, Wise . Excess NF-κB activity thus induces an ectopic odontogenesis program that is usually suppressed under physiological conditions.